The functions of catalan Educational Inspection from the Catalan Educational Law (LEC) and the centers autonomy process - Segura Torres, Joan; Silva García, Patricia (Avances en Supervisión Educativa, 2017)
Catalonia is one of the most developed community in relation to the centers autonomy. A step forward was made with of the LEC (2009) and the Centers Autonomy Decree. The role of the Educational Inspection has not been explained or revised to adapt to those new changes and how to contribute from its position. This article presents a review of all the current legislative documentation in Autonomy of Centers and Educational Inspection in Catalonia with the aim of contributing some conclusions which show us how the inspection function is positioned in developing its functions facing this situation change and suggestions about where it should lead to contribute to the improvement of educational quality. It has been carried out within the framework of the PhD Program of the Autonomous University of Barcelona.